Novel activating mutation of human calcium-sensing receptor in a family with autosomal dominant hypocalcaemia - Baran, Natalia; Braak, Michael ter; Saffrich, Rainer; Wölfle, Joachim; Schmitz, Udo (Molecular and cellular endocrinology, 2015)
Introduction - Autosomal dominant hypocalcaemia (ADH) is caused by activating mutations in the calcium sensing receptor gene (CaR) and characterised by mostly asymptomatic mild to moderate hypocalcaemia with low, inappropriately serum concentration of PTH. - Objective - The purpose of the present study was to biochemically and functionally characterise a novel mutation of CaR. - Patients - A female proband presenting with hypocalcaemia was diagnosed to have “idiopathic hypoparathyroidism” at the age of 10 with a history of muscle pain and cramps. Further examinations demonstrated hypocalcaemia in nine additional family members, affecting three generations. - Main outcome measure - P136L CaR mutation was predicted to cause gain of function of CaR. - Results - Affected family members showed relevant hypocalcaemia (mean ± SD; 1.91 ± 0.1mmol/l). Patient history included mild seizures and recurrent nephrolithiasis. Genetic analysis confirmed that hypocalcaemia cosegregated with a heterozygous mutation at codon 136 (CCC → CTC/Pro → Leu) in exon 3 of CaR confirming the diagnosis of ADH. For in vitro studies P136L mutant CaR was generated by site-directed mutagenesis and examined in transiently transfected HEK293 cells. Extracellular calcium stimulation of transiently transfected HEK293 cells showed significantly increased intracellular Ca2+ mobilisation and MAPK activity for mutant P136L CaR compared to wild type CaR. - Conclusions - The present study gives insight about a novel activating mutation of CaR and confirms that the novel P136L-CaR mutation is responsible for ADH in this family.
Gesehen am 30.07.2020